EMPLOYEE PERFORMANCE ASSESSMENT SYSTEM OF PT BPRS TANGGAMUS USING SAW AND VIKOR METHODS BASED ON MOBILE SYSTEM - Mukodimah, Siti; Priyono, Priyono; Sulaiman, Ahmad (IJISCS (International Journal of Information System and Computer Science), 2024)
Effective and accurate employee performance assessment is an important aspect in human resource management in companies, including at PT BPRS Tanggamus. However, the manual assessment system used so far is considered inefficient, time-consuming, and often less objective, causing problems in determining employee performance fairly and transparently. This study aims to develop a mobile-based Employee Performance Assessment System using the Simple Additive Weighting (SAW) and VIšekriterijumsko KOmpromisno Rangiranje (VIKOR) methods. The SAW method is used to calculate performance rankings based on several assessment criteria, while VIKOR helps in handling conflicts between criteria and producing optimal compromise solutions. This study uses a mobile system development approach integrated with a multi-criteria method, which was tested at PT BPRS Tanggamus. The results of the study show that the SAW and VIKOR-based system is able to improve accuracy, objectivity, and speed in performance assessment compared to the manual method. The mobile system also provides flexibility to management and employees in accessing assessment results anytime and anywhere, as well as increasing the transparency of the assessment process. This study recommends further development to add more complex performance analytics features, as well as improving the user interface to make the system easier to use in the future.